Adherence to the caffeine intake guideline during pregnancy and birth outcomes: A prospective cohort study - Peacock, A.; Hutchinson, D.; Wilson, J.; McCormack, C.; Bruno, R.; Olsson, C.; Allsop, Steve; Elliott, E.; Burns, L.; Mattick, R. (MDPI Publishing, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. The aims of this study were to identify: (i) the proportion of women exceeding the caffeine intake guideline ( > 200 mg/day) during each trimester, accounting for point of pregnancy awareness; (ii) guideline adherence trajectories across pregnancy; (iii) maternal characteristics associated with trajectories; and (iv) association between adherence and growth restriction birth outcomes. Typical and maximal intake per consumption day for the first trimester (T1; pre- and post-pregnancy awareness), second (T2), and third trimester (T3) were recorded for a prospective cohort of pregnant Australian women with singleton births (n = 1232). Birth outcomes were birth weight, small for gestational age, and head circumference. For each period, participants were classified as abstinent, within (≤200 mg), or in excess ( > 200 mg). Latent class growth analyses identified guideline adherence trajectories; regression analyses identified associations between adherence in each trimester and birth outcomes. The percentage of participants who reported caffeine use declined between T1 pre- and post-pregnancy awareness (89% to 68%), and increased in T2 and T3 (79% and 80%). Trajectories were: ‘low consumption’ (22%): low probability of any use; ‘within-guideline’ (70%): high probability of guideline adherence; and ‘decreasing heavy use’ (8%): decreasing probability of excess use. The latter two groups were more likely to report alcohol and tobacco use, and less likely to report planning pregnancy and fertility problems. Exceeding the guideline T1 pre-pregnancy awareness was associated with lower birth weight after covariate control (b = -143.16, p = 0.011). Overall, high caffeine intake pre-pregnancy awareness occurs amongst a significant minority of women, and continued excess use post-pregnancy awareness is more common where pregnancy is unplanned. Excess caffeine consumption pre-pregnancy awareness may increase the risk for lower birth weight. Increasing awareness of the guideline in pregn ancy and preconception health care may be warranted.